ANALISIS HUKUM TERHADAP PRAJURIT TNI YANG MELAKUKAN TINDAK PIDANA DESERSI DI WILAYAH HUKUM LANUD TGKH. M. ZAINUDIN ABDUL MADJID: Studi Kasus Putusan Nomor 23-K/PM.III-14/AU/IV/2024 & Putusan Nomor 25-K/PM.III-14/IX/2022 - Pramudaya, Vincentius; Sujono, Sujono; Sudarto, Sudarto (Neolectura, 2024)
The Indonesian National Army (TNI) is part of Indonesian society that is trained and educated to maintain the integrity of the Republic of Indonesia. TNI has a life guideline in carrying out its official life, namely Sapta Marga and the Soldier's Oath to improve discipline in the TNI's official life. However, TNI members are only ordinary people, not free from mistakes and actions related to crime. One of them is the crime of desertion during peacetime. The crime of desertion during peacetime is a crime committed by military members by mistake or intentionally being absent without permission for 30 days. This type and research is a qualitative analysis research using primary data in the form of interviews and secondary data in the form of primary legal materials, secondary legal materials and tertiary legal materials. The results of the research are to examine the problems and find answers regarding legal policies, law enforcement and future regulations regarding the crime of desertion during peacetime committed by military members in the regionlaw of TGKH Air Force Base. M. Zainudin Abdul Madjid with a case study of Judge's Decision Decision Number 23 K/PM.III-14/AU/IV/2024 & Decision Number 25-K/PM.III-14/IX/2022.